Studi Kasus Studi Kasus Pemahaman dan Penerapan Lagu Wajib Nasional di SD Negeri 81 Kota Bengkulu: Pemahaman dan Penerapan - MS, Agavin; Parmadi, Bambang; Ariffiando, Nady Febri (Jurnal PGSD, 2023)
This study aims to describe the application as well as the understanding of the obligatory national anthem in the fourth grade at SD Negeri 81 Bengkulu City. This research is qualitative research with a case study approach. The subject of this research is the teacher the fourth grade homeroom teacher and the fourth grade student. The instrument in this study was the researcher himself, using observation sheets, interviews, questionnaires, and documentation. The data validity technique is through technical triangulation and membercheck. The results showed that teachers did not always explain importance of singing the national compulsory anthem at the opening lesson. The national anthem that are often sung are the anthems Indonesia Raya, Garuda Pancasila, and Satu Nusa Satu Bangsa. For the overall understanding part, students' understanding of the seven national compulsory songs, consisting of five aspects studied, is not good enough. Students are able to mention the title, the name of the songwriter, and connect the lyrics of the song. Students have not been able to explain the meaning and the implementation of songs in daily life. So It can be concluded learning is not in accordance with the rules and students do not understand the content of song.